Spectroelectrochemical Study of a Series of Fused Oligothiophenes - Osuna,R. Malavé (2010)
Optical, electrochemical and spectroelectrochemical features of a family of triisopropylsilyl (TIPS) end-capped oligothienoacenes from the tetramer to the octamer are studied. The oxidation potentials and the formation and stability of the different oxidized species are influenced by the oligothienoacene chain length. The effect of the steric hindrance caused by the substituents on the p-dimerization of the radical cations is also investigated by comparing a trimethylsilyl (TMS) substituted pentathienoacene with a TIPS substituted one.